Phantoms and phantom limbs: history of describing the phenomenon - D. I. Korabelnikov; E. V. Tkachenko; M. O. Magomedaliev (Эпилепсия и пароксизмальные состояния)
“Phantom” is the sensation of missing body part. Phantom can occur after amputation of virtually any part of the body, but more often after amputation of the upper or lower limbs defined as a “phantom limb”. Such sensations can reach the severity of excruciating pain – phantom pain, significantly reducing the quality of patients’ life. Reports on phantoms, phantom limbs and phantom pain have been recorded since the early 16th century, but the exact underlying pathogenesis has not yet been determined, and many theories for their development have been proposed. The review discusses timeline of describing phantoms, phantom limbs and phantom pain in the scientific literature.